Pancreatoblastoma, a Rare Childhood Tumor: A Case Report - Asuman ARGON; Ahmet ÇELİK; Haldun ÖNİZ; Geylani ÖZOK; Funda YILMAZ BARBET (Federation of Turkish Pathology Societies, 2017)
Pancreatoblastoma, rarely encountered in the literature, is a malignant exocrine tumor seen in the pancreas. A 5-year-old boy suffering from abdominal pain was sent to our institute for further examination and treatment. Clinical examination was normal but for a palpable abdominal tumor mass. Abdominal Doppler ultrasonography showed a mass with well-defined margins within the body of the pancreas. Laboratory tests, including lactic dehydrogenase, alpha-fetoprotein and cancer antigen 125 were abnormal. The tumor invading the splenic vein and transverse colon was removed totally. We observed a hypercellular tumor in histopathological examination. The tumor had epithelial acinar cells and squamoid morules (corpuscles) separated by stromal bands. Adjuvant chemotherapy was used after surgery. However, the patient died 14 months later. All data about pancreatoblastoma have to be collected in order to choose the treatment to elucidate the molecular pathogenesis of the tumor, to diagnose it early and to develop target-specific treatments.